Association of Interleukin-4 in Immunoglobulin-E Mediated Asthma: A Cross Sectional Study - Hameed, Raghdah Maytham; Najim Abood, Haidar Abdul Amir; Al-Hasnawy, Huda H (Journal of Medicine, 2023)
Backgrounds: Interleukin 4 (IL 4) is a cytokine associated with the cause of several allergic diseases such as asthma due to their function in the differentiation of T helper type 2 lymphocytes and induction of the IgE isotype switch. Object: The study aims to determine the association IL-4 level with total serum IgE levels and asthma severity. Methods: A cross-section study was performed. Eighty-seven subjects were recruited from Karbala Teaching Hospital for Children in the period extending from January 25 to May 24, 2022, including children with asthma, were subjected to measure IL 4 level using Elabscience ELISA kit and measured total IgE level using AccuBind IgE ELISA kit. Results: Eighty-seven subjects of asthmatic children in which the mean age was 7.833 ± 3.652. There are 65.52% and 34.48% of asthmatic children (male and female, respectively). Total serum IgE was 398.889 ± 227.156 IU/ml, while the IL-4 level was 5.18 ± 8.224. There was a significant difference in IL 4 levels depending on asthma severity (P= 0.037). IL-4 levels in severe persistent asthma were higher than IL-4 levels in mild and moderate persistent asthma. Further, there was a highly significant difference in IL 4 levels depending on asthma controlled (P= 0.004). IL-4 levels in not well-controlled asthma were higher than IL-4 levels in well and partial controlled asthma. In addition, there was no significant correlation between IL-4 levels and total serum IgE levels (P=0.436). Conclusion: IL 4 has an important role in predicting asthma severity and asthma control in children. These findings have important implications for the treatment of IgE-mediated asthma. Despite this, IL 4 levels have no significant correlation with total serum IgE levels. J MEDICINE 2023; 24(2): 89-95